Geochemical Assessment of Environmental Impact on Groundwater Quality in Coastal Arid Area, South Eastern Tunisia - Agoubi, Belgacem; Kharroubi, Adel; Abida, Habib (Journal of Environmental Science and Engineering Technology, 2014)
Groundwater contamination has been recognized as one of the most serious problems in semi-arid and arid area (e.g. Zarzis aquifer, south-eastern Tunisia). The groundwater chemistry evolves rapidly and the salinity goes up considerably. A geochemical survey was carried out in which 23 groundwater samples were collected. EC, pH, TDS and major ions were measured and analyzed. Geochemical modeling, Piper Diagram, Q-mode hierarchical cluster and PCA were used to assess groundwater mineralization processes. Spatial variability of the different groundwater parameters was examined using semivariogram analysis. Results revealed that the Na-Cl-Ca-SO4-K is the dominant water type, suggesting rock-water interaction and dissolution of NaCl, CaSO4, 2H2O and KCl from sebkhas to be the main processes controlling groundwater mineralization in study area. Hierarchical Cluster Analysis (HCA) showed that groundwater is grouped in two clusters: the first, located in the southern part of the study area, is influenced by salt depressions in which a high potassium concentration was found. The second cluster characterized by rock-water interaction is located in the northern par of study area. Spatial development of groundwater flow and TDS were analyzed using variographic analysis and kriged maps were plotted. The method has succeeded in effectively extracting useful information, and improving the analysis of salinity and piezometric level, thereby playing an important role in qualitative and quantitative predictions. No reversal of the hydraulic gradient is detected in the study area, which eliminates any assumption on seawater intrusion in the region.